The Effect of Temperature on Age Estimation of Semen Stains on Porous Versus Non-porous Surfaces Using Messenger Ribonucleic Acid Measurement - Basma Kamal Ibrahim; Abla Abdelmeguid Attia; Laila Ahmed Rashed; Mohamed Ahmed Abd El Salam; Heba Abdo Abdel Razik (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Background: While messenger Ribonucleic Acid (mRNA) can be used to identify the type of body fluid, its degradation can also indicate the time interval since it was deposited. This study was conducted to evaluate the effect of temperature on the estimation of the age of human semen stains using mRNA deposited on porous versus non-porous surfaces at different time intervals. Methods: Ten semen samples were applied on two different media (glass and cotton) and exposed to three different temperatures (4°C, room temperature, 40°C) and examined at three-time intervals (0, 45, and 90 days). The semen-specific mRNA markers protamine 1 (PRM1) and protamine 2 (PRM2) were quantitatively assessed along with a reference gene, beta-actin, using a reverse transcription-quantitative polymerase chain reaction. Results: Mean Cq values of mRNA markers (PRM1 and PRM2) and the reference gene (beta-actin) increased with time of storage at different temperatures in both examined media. The mean quantification cycle (Cq) values of PRM2 were lower than PRM1, indicating that the levels of PRM2 marker in semen stain were higher than those of PRM1 marker. However, the mean Cq values of PRM2 at each time interval were not significantly different between temperatures, while PRM1 showed statistically significant differences in mean Cq values between temperatures at day 45 in both media. Conclusion: These results indicate that PRM2 can act as a reliable mRNA marker to estimate the time of deposition of semen stain at different temperatures on two different media.